Test for creative thinking-drawing production (TCT-DP): a revised factorial structure - Almeida, Maria Leonor Maciel dos Santos (2021)
This research aims to assess the factorial structure of the Test for Creative Thinking-Drawing Production (TCT-DP, Urban & Jellen, 1996) for a Portuguese adult sample, with620 workers, revisiting the results obtained by Almeida, Ibérico Nogueira, and Lima (2018). Two studies were performed. In Study 1, an exploratory factor analysis (EFA) assessed the factorial structure of the TCT-DP, with three hundred and two individuals(N = 302), most of them women (55.6%),from 18 to 86 years (M = 41.1, SD = 10.7). In Study 2, a confirmatory factor analyses aimed to replicate the factorial solution identified in Study 1, with three hundred and eighteen individuals(N = 318), most of them women (56.6%),from 19 to 70 years (M = 40.6, SD = 10.1). The two-factor solution (F1-Adaptiveness; F2-Innovativeness) proposed in Study 1 had acceptable to marginal fit indices. As in the study of 2018, two factors emerged and are respectively composed by the same items. Once more, the results highlight the importance of both non-conventional and conventional thinking for the creative process, sustaining our TTT-Two Tracks of Thought model.Some of the items which belong to the Adaptiveness factor, lead us to reflect on the parental features and developmental path.